Inovasi Potensi Lokal Ikan Asap Sebagai Makanan Tambahan Dalam Pencegahan Stunting Di Desa Randuputih - Ira Firnandari; Evi Tri Jayanti; Siti Nur Fauziah; Lukman Arif; Irla Rahma Sari (Cv. Utility Project Solution, 2023)
Abstract Randuputih Village, Dringu District, Probolinggo Regency has a fairly high stunting prevalence rate with a stunting rate of more than 20 percent. This shows that the problem of nutrition and child growth is still an important concern in Randuputih Village. A sustainable effort is needed to reduce the prevalence of stunting through improving nutrition. One of the efforts to deal with nutritional problems in toddlers, especially with the problem of stunting, is by providing Supplemental Food (PMT) high in energy and protein. The implementation of the innovation of shredded skipjack tuna as Supplementary Feeding (PMT) refers to the technical guidelines issued by the Ministry of Health of the Republic of Indonesia on Supplementary Feeding (PMT) which utilizes local food ingredients intended for toddlers and pregnant women. The method of community service activities uses the Focus Group Discussion (FGD) method in the form of outreach activities or counseling on the PMT innovation of smoked skipjack tuna in the context of preventing stunting in Randuputih Village. The socialization activity regarding the Innovation of Supplemental Feeding (PMT) went well and the target of the counseling participated well and is expected to contribute to reducing the stunting rate in Randuputih Village.